Modelo de um sistema MTS com ponto de pedido, lote econômico e processamento FIFO de ordens e pedidos - Rodrigues, José de Souza [UNESP]; Marinho, Mariana de Toledo [UNESP]; de Campos, Renato [UNESP]; Muniz, Jorge [UNESP]; de Souza, Fernando Bernardi [UNESP] (My University, 2016)
This paper presents the model of a productive system which was projected to supply the demand making to stock, operate with reorder point, economic production quantity and process the production orders by the rule first-in, first out. This model it was developed to teach operations in engineering courses and it was motivated by the difficult of present in integrated way the concepts of “make to stock”, “reorder point”, “economic production quantities” and rules of production orders dispatch. Nowadays, it is very common to find these concepts separated in the text books used in the undergraduate, but it is not common to find them acting together. So, it was created a model of a production system which process four products and operate under these concepts. The purpose of create the model has the intention of provide students with a model that present the dynamic behavior of a system built with these characteristics. The results obtained by simulation of the model showed that the failures of this system will depend of its initial conditions, indicating that the freezing time of the production planning it is a very important variable of planning and controlling production systems.
Model of an MTS system with reorder point, economic lot and FIFO processing of production orders and requests
Keywords: Models; MTS; PROMODEL; Simulation